Bowel dysfunction in young women with urinary retention. Issue 10 (October 1993) - Lemieux, M C; Kamm, M A; Fowler, C J
Abstract : Urinary retention in young women is rare, but a syndrome has recently been described in which urinary retention is associated with abnormal periurethral electromyography. The incidence of bowel dysfunction in these women was investigated, in an attempt to determine whether this might be a more widespread disorder. Of 12 patients with this urological abnormality, eight were constipated. No consistent anorectal abnormality was identified on anorectal physiological testing. The electromyographic abnormality was not seen in the external anal sphincter. One patient had an abnormality of the internal anal sphincter smooth muscle, while another had a generalised disorder of the gastrointestinal tract and urinary bladder resembling a visceral myopathy. Bowel symptoms are common in this group of women with urinary retention, but abnormalities of bowel function are not specific. A common mechanism for bladder and bowel symptoms remains a possibility.